1999
DOI: 10.1098/rstb.1999.0445
|View full text |Cite
|
Sign up to set email alerts
|

Neuromuscular control of prey capture in frogs

Abstract: While retaining a feeding apparatus that is surprisingly conservative morphologically, frogs as a group exhibit great variability in the biomechanics of tongue protraction during prey capture, which in turn is related to di¡erences in neuromuscular control. In this paper, I address the following three questions.(1) How do frog tongues di¡er biomechanically? (2) What anatomical and physiological di¡erences are responsible? (3) How is biomechanics related to mechanisms of neuromuscular control ? Frog species use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
61
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(63 citation statements)
references
References 43 publications
0
61
2
Order By: Relevance
“…The designation of a tissue as a muscular hydrostat indicates that the tissue has the ability to both create and supply the structural support for motion (Kier and Smith, 1985;Smith and Kier, 1989;Nishikawa, 1999). Characteristically, such a tissue capitalizes on its high water content, and hence incompressibility, to modify its form without a change of volume.…”
Section: Hydrostatic Model Of Lingual Deformationmentioning
confidence: 99%
See 1 more Smart Citation
“…The designation of a tissue as a muscular hydrostat indicates that the tissue has the ability to both create and supply the structural support for motion (Kier and Smith, 1985;Smith and Kier, 1989;Nishikawa, 1999). Characteristically, such a tissue capitalizes on its high water content, and hence incompressibility, to modify its form without a change of volume.…”
Section: Hydrostatic Model Of Lingual Deformationmentioning
confidence: 99%
“…In order to achieve this function, the tissue must possess muscle fibers that are arrayed across a large spectrum of angles and exhibit the capacity for multidirectional contraction. Hydrostatic deformation has been inferred based on tissue anatomy (Uyeno and Kier, 2005;Marshall et al, 2005), gross motor behavior (Nishikawa, 1999;McClung and Goldberg, 2000) and electromyographic recordings (Bailey and Fregosi, 2001). We propose that lingual hydrostatic deformation is best considered mechanically if the tissue is portrayed as a set of coupled units of compression and expansion.…”
Section: Lingual Myoarchitecture and Hydrostatic Deformationmentioning
confidence: 99%
“…Recent comparative studies have shown that, among anurans, toads (genus Bufo) appear to be particularly adapted for ballistic tongue projection (Nishikawa, 1999;Nishikawa, 2000). Forward-dynamic biomechanical models have shown that the paired depressor mandibulae muscles produce >90% of the force needed for ballistic tongue projection in anurans (Mallett et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…As muscles provide the necessary force, elastic potential energy is stored in elastic elements while a catch of some sort (e.g. a latch or antagonistic muscle activity) prevents the movement until a later time (Gronenberg, 1996;Nishikawa, 1999;Burrows, 2003;Wilson et al, 2003;Patek et al, 2007). In human walking, such function allows higher ankle power output than what muscle fibers could produce (for power output of muscle fibers of the ankle extensors, see Appendix 1).…”
mentioning
confidence: 99%